Coventry Production Committee, 1944 (pg. 1) (Coventry, 1944)
1944 1939-1945 "Coventry Production Committee, 1944 (pg. 1)" [HFR0089], 1944 The January 1944 issue of the 'Coventry District Production Circular' from the local Trade Union Production Committee includes two articles by Jack Jones, then Coventry District Officer of the Confederation of Shipbuilding and Engineering Unions, and campaigns against the influenza epidemic including organised gargling.